DEVELOPMENT OF LEARNING DEVICE OF EMPOWERMENT THROUGH THINKING NATURAL SCIENCE LEARNING IN ELEMENTARY SCHOOL - Jamaluddin -; Agus Ramdani; Dadi Setiadi (Jurnal Penelitian Pendidikan IPA, 2018)
The objectives of this study were to: (1) develop learning device for questioning empowerment thinking (PBMP) combined with cooperative strategies of TPS types and NHT types in science subjects in primary schools; (2) to know the different understanding of students' science concepts by applying the learning of PBMP, PBMP.TPS, PBMP.NHT and Conventional Strategy; (3) know the consistency of PBMP applications, PBMP.TPS, PBMP.NHT and Conventional Strategies. This research method: (1) research and development method to develop learning device; and (2) quasi experimental study to know the effect of applying learning tool to understanding student biology concept. To collect data using the science-biology concept test. Hypothesis test using covariance analysis technique (Ancova). The results of the research are: (1) This research produces learning device consisting of syllabus, PBMP learning plan, PBMP.TPS and PBMP.NHT. Learning device have the potential to improve understanding of science concepts in elementary schools in Mataram; (2) There is a significant difference in understanding the concepts of students following PBMP, PBMP.TPS, PBMP.NHT and conventional learning strategies